Pengembangan Buku Kerja Biologi Berbasis Pembelajaran Berdasarkan Masalah (PBL) pada Materi Biologi Kelas X SMK Negeri 2 Mandrehe Tahun Pelajaran 20222/2023 - Maher Jewirawan Hulu; Jovial Vince Hasrat Gulo; Agnes Renostini Harefa (Journal on Education, 2023)
This research was motivated by the lack of use of the Student Workbook (BKS) at SMK Negeri 2 Mandrehe which resulted in low student motivation in the learning process. This study aims to develop Problem Based Learning Student Workbooks (BKS) based on Problem Based Learning in biology class X that are empirically feasible through validation of content/material experts, linguists, design experts, assessment of subject teachers, practicality (response), and effectiveness Developed BKS. This research is a development research using quantitative methods. The tool used to collect data is a validation form which includes aspects such as content/material, language, student response questionnaires, and academic achievement tests. The results of the Content/Material Validation study reached 98% with very valid criteria; Linguist validation reaches 100% with very valid criteria; Design Expert Validation reaches a percentage of 97% with very valid criteria; teacher verification reached 97%. With a 100% validation level in the research field, this standard is very valid. For field test results obtained a percentage of 96.25% (a very practical standard), and for the effectiveness of BKS obtained a very effective standard with an achievement percentage of 85% of student learning completeness, which is a very effective standard.